Evaluation of the Impact of Risk Management and Information Security on Cybersecurity Maturity of the Institute ABC Data Management Application - Safitri, Riana; Darjat, Darjat (West Science Information System and Technology, 2024)
In the contemporary digital landscape, organizations face an escalating array of cyber threats that imperil the security and confidentiality of their data assets. This quantitative study investigates the impact of risk management strategies and information security measures on the cyber security maturity of ABC Institute's data management application. Survey data were collected from 122 employees directly engaged in data management and security roles within the institute, and Structural Equation Modeling (SEM) with Partial Least Squares (PLS) was employed for data analysis. The findings reveal significant positive associations between risk management practices, information security measures, and cyber security maturity. These results emphasize the crucial role of comprehensive risk management strategies and robust information security measures in bolstering cyber resilience. Practical recommendations stemming from this study provide actionable insights for organizations aiming to fortify their cyber security posture.